THE INFLUENCE OF ANIMATION VIDEO MEDIA ON ABILITY TO KNOW NUMBERS CONCEPTS IN CHILDREN AGED 4-5 YEARS - Laras Septiani; Rita Kurnia (Program Studi Pendidikan Guru PAUD Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2020)
This research aims to determine the effect of video animation on the ability to recognize the concept of numerals. This research was conducted in Islam Al Azhar 54 Kindergarten, Pekanbaru. This research used an experimental method with one group pretest and posttest design. The sample of 15 children and used saturated sampling technique. Data collection techniques in this research were observation techniques. Data analysis techniques used t-test and SPSS 23. The results of data analysis can be obtained t count 10.990 greater than t table 2.145 with a significance of 0.000 <0.05. It could be concluded that there were differences in knowledge about the ability to recognize the concept of numerals before and after the used of video animation media. The influence given by the video animation media based on the N Gain formula of 40.96% is in the medium category. Penelitian ini bertujuan untuk mengetahui pengaruh video animasi terhadap kemampuan mengenalkonsep bilangan. Penelitian ini dilakukan di TK Islam Al Azhar 54 Pekanbaru. Penelitian inimenggunakan metode eksperimen dengan desain one group pretest posttest dengan jumlah sampel 15orang anak dan menggunakan teknik sampling jenuh. Teknik pengumpulan data dalam penelitian iniadalah dengan teknik observasi. Teknik analisis data menggunakan uji t-test dengan menggunakanprogram SPSS 23. Hasil analisis data dapat diperoleh t hitung 10,990 lebih besar dari t tabel 2,145dengan signifikansi 0,000<0,05. Dapat disimpulkan bahwa terdapat perbedaan pengetahuan tentangkemampuan mengenal konsep bilangan sebelum dan sesudah penggunaan media video animasi.Pengaruh yang diberikan oleh media video animasi berdasarkan rumus N Gain sebesar 40,96% beradapada kategori sedang.